2001
DOI: 10.1034/j.1399-3038.2001.012003166.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement analysis in children with idiopathic membranoproliferative glomerulonephritis: A long‐term follow‐up

Abstract: Fifty children with idiopathic membranoproliferative glomerulonephritis (MPGN), aged 2-14 years at apparent onset, were monitored for the presence of C3 nephritic factor (C3 NeF) and signs of complement activation in serum. In addition, C3 allotyping was performed in 32 patients. Observation time ranged from 2 to 20 (median 11) years. C3 NeF activity was detected at least once in 60% of the patients (in 11 of 26 with type I, in 15 of 17 with type II, and in four of seven with type III). C3 NeF-positive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 34 publications
1
76
0
3
Order By: Relevance
“…By changing the balance of complement activation and inhibition C3NeF contributes to the disease, in line with the involvement of complement dysregulation in DDD (Appel et al, 2005). C3NeF, however, is also found in healthy persons and in other pathological conditions, and a clear causative relationship for C3NeF and DDD has not been demonstrated (Schwertz et al, 2001;Appel et al, 2005;Smith et al, 2007;Spitzer et al, 1990). The appearance of high-affinity C3NeF in the patients is possibly antigen-driven, due to neoepitopes exposed on activated complement components (Spitzer et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing the balance of complement activation and inhibition C3NeF contributes to the disease, in line with the involvement of complement dysregulation in DDD (Appel et al, 2005). C3NeF, however, is also found in healthy persons and in other pathological conditions, and a clear causative relationship for C3NeF and DDD has not been demonstrated (Schwertz et al, 2001;Appel et al, 2005;Smith et al, 2007;Spitzer et al, 1990). The appearance of high-affinity C3NeF in the patients is possibly antigen-driven, due to neoepitopes exposed on activated complement components (Spitzer et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…An anti-factor H miniantibody consisting of lambda light-chains, which inhibited factor H complement regulatory activity, was identified in a DDD patient (Meri et al, 1992;Jokiranta et al, 1999). C3 nephritic factor (C3NeF), an antibody against the C3bBb convertase (Spitzer et al, 1969), is found in 50-80% of DDD patients (Schwertz et al, 2001;Appel et al, 2005). C3NeF binds to a neoepitope on the newly assembled C3bBb, increases the half-life of the convertase against both intrinsic and extrinsic, factor H-mediated, decay and thus enhances C3 consumption (Daha et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…However, type II MPGN does not demonstrate immune complex or C4 deposition and shows preserved levels of C4 (62). Greater than 80% of the patients with type II MPGN have circulating autoantibodies, termed nephritic factors, that bind the alternative pathway convertase C3bBb (62)(63)(64). These nephritic factors stabilize the C3bBb complex and prolong its half-life.…”
Section: Type II Membranoproliferative Glomerulonephritis (Mpgn)mentioning
confidence: 99%
“…In AMD and diseases such as Alzheimer's (17), atherosclerosis (18), and glomerulonephritis (19), characteristic lesions and deposits contribute to disease pathogenesis and progression. Although the molecular bases of these diseases may be diverse, the deposits contain many shared molecular constituents that are attributable, in part, to local inflammation and activation of the complement cascade, a key element of the innate immune system in host defense.…”
mentioning
confidence: 99%